EFEKTIFITAS PEMBERIAN PUPUK HAYATI TERHADAP PERTUMBUHAN DAN HASIL PADI GOGO PADA TANAH KERING - Agus Supriyo; S. Minarsih S. Minarsih; B. Prayudi B. Prayudi (Universitas Muhammadiyah Purwokerto, 2014)
On-farm experimental were conducted in dry land of Banyusri villages, Wonosegoro sub district, Boyolali district in 2013/2014 WS. Randomizied block designed was used with four replications. Eight treatments consisted of fertilizers based on Dry soil test kit as control (P1), 50% NPK fertilizers recommended + Probio (P2), 50% NPK fertilizers recommended + Remicer (P3), 50% NPK fertilizers recommended + Starmik + 2 t FYM/ha (P4), 50% NPK fertilizers recommended + Agrimeth (P5), 50% NPK fertilizers recommended + Biovam plus (P6), 50% NPK fertilizers recommended + Glyocompoct (P7), 50% NPK fertilizers recommended (P8), 50% NPK fertilizers recommended + 2 t FYM/ha (P9). Parameters were observed i.e. plant growth (plant height and tiller numbers per hills), rice yield (converse plot sized 2.5 m x 2.5 m in hectares at 14 % water contents) and farmer respons on biofertilizers used were evaluated. Research resulted showed thats (a) the applicaton of biofertilizers such as Probio, Glyocompost and Starmix were combined to 50% NPK fertilizers recommended gave the rice yield same with combined to NPK fertilizers recommended, its means that usage recommendation of 50% NPK fertilizers combined to third biofertizers able to 50% NPK fertilizers efficient. (b). The farmer respons to usage of biofertilizers applied showed that (b1) 83.3% cooperator farmers positive respons in application of biofertilizer. (b2) 61.20 % farmers most easierly on biofertilizers applied. (b3) 94,4% farmers has benefit from biofertilizers applied. (b4) 83,3 % cooperators farmer able to buy biofertilizers in the markets. (b4) Cooperator farmers to select in liquid forms of biofertiliers with Rp 10.000 per sacheet prices. But if solid type of biofertilizers with prices Rp 1.000,- per kg. Keywords : efectivness, biofertilizer, gogo rice